2022
DOI: 10.1088/1755-1315/1055/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

The presence of microplastics in fishes of South Maldives

Abstract: Plastic pollution has been a widespread global challenge with negative impacts on human health, environment and economies. Recently its effect on the environment and marine life has been of immense interest. This study aimed to investigate the presence of microplastics in the gut, gill and flesh of Selar Crumenophthalmus and Decapterus Macarellus from two different locations in South Maldives. A total of 56 fishes were examined from the two species and a total of 200 possible microplastic pieces were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Among the polymers found, PE (55%) and PP (33%) were by far the most abundant. Nearer to the Bangladeshi coastline, namely in the Sundarban's estuary, in 2022, Sultan et al [49] ing that respectively 80% and 76% of the fish had ingested MP [191]. Big-eye scad carried 4.03 ± 5.6 MP/fish (0.02 MP/g), while mackerel scad was found with 2.19 ± 2.0 MP/fish (0.04 MP.g) [191].…”
Section: Microplastic Abundance In Fish Species In the Indian Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the polymers found, PE (55%) and PP (33%) were by far the most abundant. Nearer to the Bangladeshi coastline, namely in the Sundarban's estuary, in 2022, Sultan et al [49] ing that respectively 80% and 76% of the fish had ingested MP [191]. Big-eye scad carried 4.03 ± 5.6 MP/fish (0.02 MP/g), while mackerel scad was found with 2.19 ± 2.0 MP/fish (0.04 MP.g) [191].…”
Section: Microplastic Abundance In Fish Species In the Indian Oceanmentioning
confidence: 99%
“…Nearer to the Bangladeshi coastline, namely in the Sundarban's estuary, in 2022, Sultan et al [49] ing that respectively 80% and 76% of the fish had ingested MP [191]. Big-eye scad carried 4.03 ± 5.6 MP/fish (0.02 MP/g), while mackerel scad was found with 2.19 ± 2.0 MP/fish (0.04 MP.g) [191]. Silva et al reported MP contamination in fish and mussels in southern coastal waters of Sri Lanka [204].…”
Section: Microplastic Abundance In Fish Species In the Indian Oceanmentioning
confidence: 99%